Strategies Used in the Translation of Hidden Potential - Tiffany Vivian Wijaya; Julia Eka Rini (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
In translating, difficulties often emerge during the translation process. In translating the book entitled Hidden Potential written by Wendy Pope from English to Bahasa Indonesia, Mona Baker’s translation strategies are used to overcome the difficulties that emerge in the translation process. The strategies used are as follows: translation by a more general word, translation by a more neutral word, translation by cultural translation, and translation by omission. The strategy of translation by illustration is not used since this book contains only words without any pictures or illustrations.